Application of Optimum Compaction Energy in the Development of Bricks Made with Construction Trash Soils - T. Lopez-Lara; C. L. Gonzalez-Vega; J. B. Hernandez-Zaragoza; E. Rojas-Gonzalez; D. Carreón-Freyre; R. Salgado-Delgado; E. Garcia-Hernandez; M. Cerca (Advances in Materials Science and Engineering)
In general, bricks frequently show different densities and therefore different resistances because the compaction energy is not considered in their production. Expansive soils represent a problem for light buildings over them because of volumetric instability. A generalized solution has been to extract them and substitute them by inert soil; thus they become construction trash. So, in this work the compaction energy aspect and the use of construction trash soils in the elaboration of resistant masonry bricks of homogeneous and controlled density are a new contribution in the production of bricks of better quality. First, the soil was stabilized with CaOH which leads to a decrease in its volumetric changes. Then, they were compacted with a specific energy for obtaining an optimal and maximum controlled density to ensure an increase in strength. Our results show that two optimal compaction energies can be considered with respect to the variation of optimum moisture in masonry bricks of expansive soil stabilized with lime. The first is when the optimal humidity reaches its smallest value (integrated soil lumps) and the second is when humidity increases (disintegrated soil lumps), after reaching its lowest value. We also conclude that high compaction energy does not improve density values.